EVALUATING THE EFFECTIVENESS OF NURSING INTERVENTIONS AND PATIENT EDUCATION ON HEALTH OUTCOMES IN A RURAL HEALTH CENTER: A COLLABORATIVE APPROACH - Fatimah Mohammed B Aljameeli, Kawakib Saeed Mudhhi Aljameeli, Entisar Muklef Mohamed AljemeeliFaoziah Saleh E Alhoraigi, Faoziah Saleh E Alhoraigi, Ahlam Mohammed Mudhhi Alsaadi, Seham Mutlaq Saad Aljamili, (Chelonian Research Foundation, 2022)
Nursing interventions and patient education play a crucial role in promoting health outcomes, particularly in rural health centers where access to healthcare resources may be limited. This study aimed to evaluate the effectiveness of nursing interventions and patient education on health outcomes in a rural health center in Hafar Al-Batin, Saudi Arabia, using a collaborative approach among nursing staff. A mixed-methods research design was employed, involving a retrospective analysis of patient records, a survey of nursing staff, and focus group discussions. The findings revealed that nursing interventions and patient education had a significant positive impact on health outcomes, including improved patient knowledge, adherence to treatment, and reduced hospital readmissions. The collaborative approach among nursing staff was found to be effective in enhancing the quality of care and patient satisfaction. The study highlights the importance of investing in nursing interventions and patient education in rural health centers and provides valuable insights for healthcare policy and practice in Saudi Arabia. Keywords: nursing interventions, patient education, health outcomes, rural health center, collaborative approach